2010
DOI: 10.1007/s11064-010-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Brain Extracellular Dopamine and Glycine Levels Following Combined Administration of the Glycine Transporter Type-1 Inhibitor Org-24461 and Risperidone

Abstract: The most dominant hypotheses for the pathogenesis of schizophrenia have focused primarily upon hyperfunctional dopaminergic and hypofunctional glutamatergic neurotransmission in the central nervous system. The therapeutic efficacy of all atypical antipsychotics is explained in part by antagonism of the dopaminergic neurotransmission, mainly by blockade of D(2) dopamine receptors. N-methyl-D-aspartate (NMDA) receptor hypofunction in schizophrenia can be reversed by glycine transporter type-1 (GlyT-1) inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
1
15
0
3
Order By: Relevance
“…Our data showing that α3 GlyRs mediate tonic currents in brain suggest that glycine itself probably serves as the main endogenous GlyR ligand in the forebrain. Low micromolar concentrations of ambient glycine are present in the cerebrospinal fluid (59), and there are multiple sources for extracellular glycine, including glycinergic neurotransmission (60), synaptic corelease with glutamate or GABA (61)(62)(63)(64), and release from astrocytes (65,66). Further studies are necessary to determine the specific sources of glycine responsible for the tonic activation of GlyRs.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showing that α3 GlyRs mediate tonic currents in brain suggest that glycine itself probably serves as the main endogenous GlyR ligand in the forebrain. Low micromolar concentrations of ambient glycine are present in the cerebrospinal fluid (59), and there are multiple sources for extracellular glycine, including glycinergic neurotransmission (60), synaptic corelease with glutamate or GABA (61)(62)(63)(64), and release from astrocytes (65,66). Further studies are necessary to determine the specific sources of glycine responsible for the tonic activation of GlyRs.…”
Section: Discussionmentioning
confidence: 99%
“…D -serine, like glycine, is also a co-agonist of the NMDA receptors. However, it is unlikely that D -serine is the endogenous agonist that mediates the effects of GlyT1 inhibition as injection of GlyT1 inhibitor elevates extracellular glycine but not serine and glutamate levels in the brain of rats41. Future studies are necessary to dissect the specific role of glycine versus serine per se as well as in the presence of GlyT1 inhibition in regulating glucose and energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the extracellular levels of glutamate were also enhanced. This study suggests that co-administration of an antipsychotic drug with a GlyT-1 inhibitor could normalize hypofunctional NMDA receptor-mediated glutamatergic neurotransmission with reduced dopaminergic side effects characteristic for antipsychotic medication [58].…”
Section: Sarcosine-derived Glyt-1 Inhibitorsmentioning
confidence: 80%
“…Both NFPS and Org24461 (1-10 mg/kg) reversed PCP-induced changes in EEG power spectra in conscious rats. Recently, it has been reported that co-administration of Org24461 and antipsychotic drug risperidone caused a decrease of extracellular dopamine levels accompanied with sustained elevation of extracellular glycine levels [58]. Interestingly, the extracellular levels of glutamate were also enhanced.…”
Section: Sarcosine-derived Glyt-1 Inhibitorsmentioning
confidence: 98%